2020
DOI: 10.17679/inuefd.535845
|View full text |Cite
|
Sign up to set email alerts
|

A Literature Review on the Issues Encountered in Educating Syrian Children in Turkey

Abstract: The biggest migration in Turkey's history began in 2011 with the beginning of the civil war in Syria. Approximately 3.6 million citizens of Syria have logged in Turkey since then. According to data published by The Directorate General of Migration Management 2018, about 1.6 million of these Syrians in Turkey are children in the school-age and young people that age in higher education. It cannot be ignored the importance of educating as qualified individuals such a great number of people not only for the future… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(7 citation statements)
references
References 14 publications
(25 reference statements)
0
6
0
1
Order By: Relevance
“…In addition to neglect in the domestic environment, immigrant children may also be deprived of adequate social resources that support their development. For instance, a significant number of these children do not continue their education due to reasons such as language barriers and economic difficulties (Tunga et al, 2020), while children who continue their education experience exclusion and problems in peer relations (Türker & Göçmenler, 2020). In this regard, it can be suggested that children who do not have opportunities to socialize successfully may have difficulty in developing adequate self-control and resilience.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to neglect in the domestic environment, immigrant children may also be deprived of adequate social resources that support their development. For instance, a significant number of these children do not continue their education due to reasons such as language barriers and economic difficulties (Tunga et al, 2020), while children who continue their education experience exclusion and problems in peer relations (Türker & Göçmenler, 2020). In this regard, it can be suggested that children who do not have opportunities to socialize successfully may have difficulty in developing adequate self-control and resilience.…”
Section: Discussionmentioning
confidence: 99%
“…One might predict that the challenges brought by being a refugee become more visible or adverse in an environment where the child has to receive education in a new community language (Tsimpli et al, 2020). Language barrier does not only make the social adaptation difficult but also being immersed in a medium of instruction that is different from one's mother tongue may not allow the refugees to meet their academic potential (Cahan et al, 2001;Frumkin, 2013;Ibragimova & Tarasova, 2018;Tunga et al, 2020), which in turn may cause delays in cognitive development (Parisi et al, 2012).…”
Section: Language Experiences Of Displaced and Immigrant Childrenmentioning
confidence: 99%
“…In the interviews with the teachers of the Syrian students placed in the Ministry of National Education, the teachers stated that the only criterion used for the placement of these students in the schools affiliated to the Ministry of National Education is their age and emphasized that the students have different language proficiency despite being the same age (Tunga et al, 2020). Another reason for not overcoming the language barrier was stated as the inadequacy of the course materials used in Turkish teaching.…”
Section: Language Barriermentioning
confidence: 99%